CRISPR-mediated gene silencing reveals involvement of the archaeal S-layer in cell division and virus infection - Isabelle Anna Zink (Nature Portfolio, 2019)
The S-layer is a proteinaceous envelope often found in bacterial and archaeal cells. Here, the authors use CRISPR-based technology to silence slaB, encoding the S-layer membrane anchor, to show that an intact S-layer is important for cell division and virus susceptibility in the archaeon Sulfolobus solfataricus.